101k views
0 votes
Solve the equation.

Give your simplified answer as an improper fraction.
3(x - 1) = 2(3 – x)
? you

Solve the equation. Give your simplified answer as an improper fraction. 3(x - 1) = 2(3 – x-example-1
User Chromigo
by
5.1k points

2 Answers

3 votes

Answer:

3(x-1)=2(3-x)

3x-3=6-2x

3x+2x=6+3

5x=9

divide both sides by 5

  • Answer
  • x=9
  • 5

Explanation:

multiply 3 by x -1 and x 3 x - 1

step 2: after simplifying collect like terms

solve from there

User JcT
by
4.9k points
4 votes

Answer:

3(x_1)=2(3_x)

or,3×_3 =6_2×

or,3×+2× =6+3

or,5× =9

or,× =9/5

User Schnee
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.